Comparison Among Two Liquid Formulations of L-thyroxine in the Treatment of Congenital Hypothyroidism in the First Month of Life: A Pilot Study - Tuli, Gerdi; Munarin, Jessica; de Sanctis, Luisa (Frontiers in Endocrinology, 2022)
The liquid formulation of L-thyroxine is the most used in the substitutive treatment of congenital hypothyroidism (CH). This formulation has higher TSH suppression rates with respect of L-thyroxine tablets and thus lower doses are indicated. Two types of liquid L-thyroxine (Tirosint© and Tifactor©) are currently approved in Italy for use in pediatric age and to date there are no data available in the Literature comparing the two liquid formulations. The aim of this study is to compare the efficacy of both formulations in normalizing TSH and fT4 levels in the first month of life and to compare the L-thyroxine requirement for both formulations over the same period. All newborns diagnosed with primary CH at the neonatal screening program in the Piedmont region of Italy in the period May 2020 – May 2021 were enrolled and divided into two groups according to the liquid formulation used: TS Group with Tirosint© and TF Group with Tifactor©. No difference was observed between the two groups considering the TSH at dried blood spot (DBS) at neonatal screening, the serum levels of TSH, fT4 and fT3 and initial dose of L-thyroxine. At 15 days the serum TSH in the TF Group was 0.08 ± 0.02 mcUI/ml, while in the TS Group it was 36.7 ± 14.7 mcUI/ml p=0.04). No differences were observed between the two groups considering fT4 levels and L-thyroxine requirement. Among the subjects in the TF Group, 5/9 showed suppressed TSH at 15 days after starting treatment, while none of the subjects in the TS Group showed TSH levels below the normal lower limit (p=0.011). Among the subjects in the TF Group, 5/9 patients showed suppressed TSH at 30 days after starting treatment, while 1/12 subjects in the TS Group showed TSH levels below the normal lower limit (p=0.017). In conclusion, this study confirms the efficacy in normalizing the thyroid hormonal profile in newborns with CH among the liquid solutions although the response seem to be different in timing therefore an individual approach is necessary considering the type of formulation used, the diagnostic category of CH and clinical features.